IPSC-derived cortical neurons to study sporadic Alzheimer disease: A transcriptome comparison with post-mortem brain samples. (1st March 2022) - Verheijen, M.C.T; Krauskopf, J.; Caiment, F.; Nazaruk, M.; Wen, Q.F.; van Herwijnen, M.H.M.; Hauser, D.A.; Gajjar, M.; Verfaillie, C.; Vermeiren, Y.; De Deyn, P.P.; Wittens, M.M.J.; et al.
Highlights: The transcriptome of iPSC-derived cortical neurons and brain biopsies were assessed. sAD iPSC-derived neurons & brain samples showed many similar AD-related processes. iPSCs exposed to toxicants increases our knowledge of their AD-inducing properties. Abstract: Alzheimer's disease (AD) is the most common cause of dementia, characterized by the progressive impairment of cognition and memory loss. Sporadic AD (sAD) represents approximately 95 % of the AD cases and is induced by a complex interplay between genetic and environmental factors called "Alzheimerogens". Heavy metals ( e.g. copper) and pesticides ( e.g. fipronil) can affect many AD-related processes, including neuroinflammation (considered as AD-inducing factor). Research would benefit from in vitro models to investigate effects of Alzheimerogens. We compared transcriptomics changes in sAD induced pluripotent stem cell (iPSC) derived cortical neurons to differentially expressed genes (DEGs) identified in post-mortem AD brain tissue. These analyses showed that many AD-related processes could be identified in the sAD iPSC-derived neurons, and furthermore, could even identify more DEGs functioning in these processes than post-mortem AD-brain tissue. Thereafter, we exposed the iPSCs to AD-inducing factors (copper(II)chloride, fipronil sulfone and an inflammatory cytokine cocktail). Cytokine exposure induced expression of immune related genes while copper-exposure affected genes involved in lipid and cholesterol metabolism, which are known AD-related processes. Fipronil-exposure did not result in significant transcriptomic changes, although prolonged exposures or higher doses may be necessary. Overall, we show that iPSC-derived cortical neurons can be beneficial in vitro models to identify Alzheimerogens and AD-related molecular mechanisms.